Coxsackievirus B4 myocarditis and meningoencephalitis in newborn twins. Issue 5 (7th April 2014) - Bissel, Stephanie J.; Winkler, Caitlin C.; DelTondo, Joseph; Wang, Guoji; Williams, Karl; Wiley, Clayton A.
<x xml:space="preserve">Abstract</x> Coxsackievirus B4 (CB4) is a picornavirus associated with a variety of human diseases, including neonatal meningoencephalitis, myocarditis and type 1 diabetes. We report the pathological findings in twin newborns who died during an acute infection. The twins were born 1 month premature but were well and neurologically intact at birth. After a week they developed acute lethal neonatal sepsis and seizures. Histopathology demonstrated meningoencephalitis and severe myocarditis, as well as pancreatitis, adrenal medullitis and nephritis. Abundant CB4 sequences were identified in nucleic acid extracted from the brain and heart. In situ hybridization with probes to CB4 demonstrated infection of neurons, myocardiocytes, endocrine pancreas and adrenal medulla. The distribution of infected cells and immune response is consistent with reported clinical symptomatology where systemic and neurological diseases are the result of CB4 infection of select target cells.